A solid strategy to realize heteroface selective emitter and rear passivated silicon solar cells. (31st May 2022) - Zou, Shuai; Ye, Xiaoya; Ding, Jianming; Wu, Chengkun; Wang, Shaozhou; Scardera, Giuseppe; Abbott, Malcolm; Zhang, Yu; Fan, Ronglei; Xu, Yadong; Wang, Xusheng; Shen, Mingrong; et al.
Abstract: Passivated emitter and rear cell (PERC) with laser‐doped selective emitter (SE) has become mainstream in the PV industry. In this work, we report a solid strategy to realize heteroface monocrystalline silicon (mono‐Si) wafers for PERC‐SE solar cells by employing alkaline polishing to form a polished surface for the rear side and well‐established metal‐catalyzed chemical etching to form a honeycomb texture for the front side in one wet process successively. The key to success lies in the fact that the two back‐to‐back wafers inserted into one slot in the cassette are tightly attached together in MCCE etching so that only the exposed surfaces are etched to form textures, while the rear polished surfaces are still retained to avoid wrap‐around etching. With the strategy, the mono‐Si PERC‐SE solar cells achieve an average efficiency of over 22.0%, no poorer than that of the reference system (traditional alkaline texturing and rear acidic polishing), and have good light trapping capability for oblique incident light. Moreover, the total Si removal in the novel process is only ~0.4 g, which is far less than that in the traditional process. More importantly, the strategy can also double the throughput of existing texturing processes and significantly reduce the amount of etching waste. Therefore, the work is expected to provide a promising way to mass produce efficient mono‐Si PERC‐SE solar cells with a superior rear surface, achieved without increasing the number of processing steps, and lower cost. Abstract : We report a solid strategy to realize heteroface mono‐Si wafers for PERC‐SE solar cells, by employing alkaline polishing for the rear and well‐established MCCE etching to form honeycomb texture for the front in one wet process successively. It can double the throughput of existing texturing processes and reduce the etching wastewater.